Impact of digital city competitiveness on total factor productivity in the commercial circulation industry: evidence from China’s emerging first-tier cities - Meng, Tiantian; Yu, Danni; Ye, Ludi; Yahya, M.H.; Zariyawati, M.A. (Springer Nature, 2023)
In the age of rapid technological advancement, the proliferation of digital technologies has reshaped urban landscapes, affecting economic, social, and environmental dynamics. Urban digital transformation is more than just a technological innovation; it stands at the core of future urban competitive strategies. As this trend evolves, the commercial circulation industry is poised for significant opportunities. However, the academic exploration into the relationship between the level of urban digitalization and the total factor productivity of the commercial circulation industry remains limited. To address this gap, this study employs data from 15 emerging first-tier cities in China. Initially, a Digital City Competitiveness Index was established, with results indicating Hangzhou taking the lead, while other cities were categorized into distinct tiers. Utilizing a two-way fixed-effects model, the research then investigates the impact of digital city competitiveness on the total factor productivity of the commercial circulation industry. The findings suggest that digital city competitiveness significantly enhances the total factor productivity within this industry. Furthermore, the study examines the influences of various sub-dimensions of digital city competitiveness on total factor productivity. Notably, investments in urban information infrastructure emerge as the most pronounced positive factor, followed by industrial development, innovation, services, and governance. In contrast, the urban ecosystem dimension exerts a negative impact. This research fills an existing void in the literature concerning the relationship between digital city competitiveness and total factor productivity, offering profound insights into the interplay between digital city development and its economic benefits. In addition, the conclusions provide policy implications for decision-makers, highlighting the importance of bolstering urban information infrastructure, encouraging enterprises to innovate, fostering industrial clusters, enhancing urban service capabilities through digital means, elevating public participation, and emphasizing environmental conservation.